PENGARUH RISIKO KREDIT, RISIKO LIKUIDITAS, EFISIENSI MANAJEMEN TERHADAP PROFITABILITAS MELALUI PERMODALAN - Chairul Adhim (Jurnal Bisnis dan Manajemen, 2018)
This study aims to determine the effect of credit risk, liquidity risk, management efficiency to profitability mediated by capital in Banking company listed on the Indonesia Stock Exchange in the period of 2010-2014. This research is an explanatory research that consists of the whole of 26 Banks listed on the Indonesia Stock Exchange in the period of 2010-2014 as sample. Thus, this study used saturated sampling technique which is involving all numbers of population. In addition, path analysis uses in this study as data analysis. The result shows that credit risk, liquidity risk and management efficiency have direct negative and significant effect to capital. Then, Credit risk, and management efficiency have a direct negative and significant effect on profitability. Moreover, liquidity risk have no direct effect on profitability. While, capital has a direct positive and significant effect on profitability. Finally, the result indicates that credit risk, liquidity risk, management efficiency have significant indirect effect to profitability through capital. DOI : https://doi.org/10.26905/jbm.v5i1.2323